Efficient microwave-assisted synthesis of hydroxymethyl ketones using NHC organocatalysts - Nikolaou, A.; Kokotos, G.; Magrioti, V. (Tetrahedron, 2016)
Hydroxymethyl ketones are useful auxiliaries in organic synthesis and are also found in several medicinal agents. N-Heterocyclic carbenes (NHCs) have been used in the literature in order to introduce the hydroxymethyl group into aromatic aldehydes in good yields, but they are not that successful for aliphatic aldehydes. In the present work, the use of microwave irradiation has been efficiently incorporated into this organocatalytic synthesis of aromatic, but more importantly of aliphatic hydroxymethyl ketones that can be used as precursors for medicinally interesting compounds.